2012
DOI: 10.1615/critrevimmunol.v32.i4.50
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity of T Cells and Its Role in the Immune System

Abstract: T-cell receptors recognize peptides presented by the major histocompatibility complex (MHC) on the surface of antigen-presenting cells (APC). The ability of the T-cell receptor (TCR) to recognize more than one peptide-MHC structure defines cross-reactivity. Cross-reactivity is a documented phenomenon of the immune system whose importance is still under investigation. There are a number of rational arguments for cross-reactivity. These include the discrepancy between the theoretical high number of pathogen-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 161 publications
2
91
2
3
Order By: Relevance
“…The issue of peptide cross-reactions by normal TCRs has long been considered important to allow responses to the diverse repertoire of potential epitopes [50,51]. It has been suggested that this cross-reactivity is due in part to the conformational plasticity of the CDRs of a TCR, combined with the low affinities required for CD8 T cell activity.…”
Section: Cross-reactivities Mediating Off-target Toxicitiesmentioning
confidence: 99%
“…The issue of peptide cross-reactions by normal TCRs has long been considered important to allow responses to the diverse repertoire of potential epitopes [50,51]. It has been suggested that this cross-reactivity is due in part to the conformational plasticity of the CDRs of a TCR, combined with the low affinities required for CD8 T cell activity.…”
Section: Cross-reactivities Mediating Off-target Toxicitiesmentioning
confidence: 99%
“…In essence, these models need to be able to understand the processes that govern the affinity between a TCR and epitope on a molecular level. This process is rather complex, because while sequence similarity seems to be related to the binding process, epitopes can be bound by varying TCRs (10)(11)(12) and TCRs can also display crossreactivity (13). Despite the advent of single cell TCR paired chain sequencing, currently available TCR-epitope binding data mostly consists of single-chain, often beta-chain, data, while in reality both the alpha-and beta-chains are thought to contribute to binding specificity.…”
Section: Introductionmentioning
confidence: 99%
“…5). Heteroclitic behavior is best documented with clonal TCR in response to peptides with amino acid substitutions at TCR or MHC contacts but how one clone reflects on the bulk polyclonal response is less clear and dependent on previous antigenic exposures (12, 57, 60-62). Furthermore the priming antigen whether NFM 15-35 or MOG 35-55 could lead to asymmetry or skewedness of the immune response based on divergent expansion of unique T cell clones.…”
Section: Discussionmentioning
confidence: 99%